Improving Procedure Text Writing Skills Using Video Media at SMP Negeri 1 Pangaribuan in Class IX - Gultom, Goklas Hasiholan (EDUCTUM: Journal Research, 2023)
The research was conducted with the main aim of improving the ability to write procedural texts through the use of video media in English learning for class IX students at SMP Negeri 1 Pangaribuan. This research was conducted in class IX of SMP Negeri 1 Pangaribuan involving two cycles. In this first cycle, the students' ability to write procedural texts was still low with an average score of 51.90. As many as 80.95% or 17 out of 21 students did not reach the minimum completeness criteria score, namely 73 and only 19.05% or 4 out of 21 students achieved the minimum completeness criteria score (KKM). The number of students who did not complete was much greater than the number of students who achieved a complete score, namely 73. 3. Meanwhile, in cycle II, results were obtained with an average score of 75. There were 76.20% or 16 out of 21 students. has reached the KKM score and only 23.80% or 5 out of 21 students are still below the KKM standard. This means that the number of students who achieved a complete score on the ability to write procedural texts using video media was greater than the number of students who did not complete it. Based on these data, it can be concluded that the use of video media in learning English can improve the ability to write procedural texts in Class IX students at SMP Negeri 1 Pangaribuan.